(untitled) (Journal of Misan Researches, 2024)
Praise be to Allah, we praise Him, seek His assistance, seek His forgiveness, and seek refuge in Him from the evils of ourselves and the wickedness of our actions. Whomever Allah guides, there is no one who can lead him astray, and whomever Allah leads astray, there is no one who can guide him. I bear witness that there is no deity worthy of worship except Allah alone, without any partners, and I bear witness that Muhammad is His servant and messenger, the most sincere advisor and the greatest conveyer of the message. Now, Allah has sent His messenger with guidance and the true religion to make it prevail over all other religions, as a witness, a bearer of glad tidings, and a warner, calling to Allah with His permission, and a shining lamp, as Allah says: "It is He who sent His Messenger with guidance and the religion of truth to manifest it over all religions, although those who associate others with Allah dislike it." (Surah At-Tawbah: 33 We acknowledge the blessing of Allah upon us by sending His Prophet Muhammad, peace be upon him, the unlettered Prophet, the truthful one, the bearer of glad tidings, and the warner. He conveyed the message of his Lord to all of humanity and illuminated the path of life with the Noble Quran and the Prophetic traditions. In this message, humanity found guidance for life, knowledge, and wisdom that they were previously unaware of. The world will continue to seek these gifts until the Day of Judgment. O Allah, bestow peace and blessings upon our Prophet Muhammad and upon his family and companions, all of them.